2006
DOI: 10.1636/t04-18sc.1
|View full text |Cite
|
Sign up to set email alerts
|

The Prey of the Lynx Spider Oxyopes Globifer (Araneae, Oxyopidae) Associated With a Semidesert Dwarf Shrub in Azerbaijan

Abstract: The prey of the lynx spider, Oxyopes globifer Simon 1876, occurring on Salsola nodulosa (Moq.) plants, was analyzed. In common with other cursorial spiders, the percentage of feeding specimens in the population of O. globifer was low (5.5%). Males were observed feeding significantly less frequently than females and immatures of both sexes. After oviposition, however, the records of prey capture in eggguarding females also declined considerably. Oxyopes globifer is a polyphagous predator feeding on a wide range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…Most of the prey of O. lineatus (87.5%) were smaller than the spiders, while those larger than their captors usually did not exceed 150% of the spider's length. The mean value and range of relative length of prey of O. lineatus were comparable to those recorded in other lynx spiders (Nyffeler et al 1987a, b, 1992, Huseynov 2006).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Most of the prey of O. lineatus (87.5%) were smaller than the spiders, while those larger than their captors usually did not exceed 150% of the spider's length. The mean value and range of relative length of prey of O. lineatus were comparable to those recorded in other lynx spiders (Nyffeler et al 1987a, b, 1992, Huseynov 2006).…”
Section: Discussionsupporting
confidence: 79%
“…The present study which revealed a high level of worker ant predation by O. lineatus (ca. 20% of the total diet) supports the hypothesis that myrmecophagy is a common phenomenon within the genus Oxyopes and probably the whole family Oxyopidae (Huseynov 2006). However, unlike other myrmecophagic cursorial spiders from the families Salticidae, Gnaphosidae, Thomisidae, and Zodariidae, which have evolved a highly specialized predatory behaviour against worker ants (Soyer 1953, Heller 1976, Oliveira & Sazima 1984, 1985, Li & Jackson 1996, Pekar 2004, almost nothing is known about the adaptations that allow lynx spiders to subdue this well-defended prey, except for speculation by Baehr & Baehr (1987) about the role of leg spines in protection of O. ramosus against ants.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations